Household Responsibilities, Spousal Support, and Gender Equality: Public Attitudes in Uzbekistan and Central Asia - Dilafruz Kuchkorova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This study examines public perceptions of gender roles, household responsibilities, and women’s career advancement in Uzbekistan, drawing on comparative data from the Life in Transition Survey IV. While female labor force participation is increasing, cultural norms and spousal attitudes continue to influence the opportunities available to women. Findings reveal that although most respondents support shared household and childcare duties, traditional expectations persist, particularly regarding women’s domestic roles. Public acceptance of equal income contribution between spouses is widespread, yet strong agreement levels are lower than in neighboring Central Asian countries. The analysis highlights the nuanced interplay between progress toward gender equality and enduring traditional norms, offering insights for policymakers and advocates of women’s economic empowerment.